A MEDIA INNOVATION PROGRAM FOR HEALTH EDUCATION AT SD INPRES KEPI, SOUTH PAPUA, TO INTRODUCE REPRODUCTIVE HEALTH EDUCATION - Rosmawati, Elly; Tangdilian, Roberth; Arfah, Muh (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
AbstractCases of sexual violence against children in the outermost, deepest, and most disadvantaged areas, such as South Papua, are still a sensitive issue and receive little attention, especially due to the lack of access to contextual reproductive health education. Students in grades 5 and 6 at SD Inpres Kepi, Mappi Regency, will learn about the personal body and what they may and cannot touch through this educational exercise. The approach involves face-to-face delivery of visual media, such as animated films and illustrated pamphlets, as part of participatory education. According to the findings, pupils can recognize private body areas, differentiate between safe and hazardous touches, and name which people are reliable sources of information. The students’ responses were very positive, shown by their active involvement in discussions and simulations. Educational media was considered effective because it was able to simplify sensitive material and improve children’s understanding. Reproductive health education based on simple and visual media has been proven to be effective in remote areas with limited resources.